WACANA KESETARAAN GENDER DALAM AL-QUR'AN DAN HADIS MENURUT HUSEIN MUHAMMAD - Andi Rabiatun (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2018)
The thought of Husein Muhammad regarding the teachings of Islam in society still raises many questions in the world of Qur’anic study and Hadith, especially his thoughts on the relation between men and women known as gender equality. As a person who wrestles in the world of pesantren, this gender deviation takes place because of the perspective of societys influenced by religious doctrines, in this classical Islamic literature is considered biased toward women. The mainstream interpretation by the classical scholars is still believed by the majority of Muslim societies to this day, still placing men as superior beings against women. This perspective is clearly contrary to the ideals of the Qur’an itself, namely equality and freedom to determine life’s choices without any threat and violence or coercion from anyone. The interpretation that is considered biased towards women, caused by mistakes in interpreting religious texts, does not occur because of the inability to interpret a text, but because of the sociocultural influence on the interpreter in which they live, involved in interpreting the texts . Not only that, the taking of traditions of the Prophet as explanation and advocate of opinion of scholars sometimes not known the quality, not shahih, maudhu ‘even dai’f. Husein’s ideas are different from other Islamic feminists. The peculiarity of Husein’s ideas in carrying the discourse of Islam and gender is the depth of Islamic classical literature in analyzing or counterarging arguments against gender inequalities in societies rarely shared by other feminists. It is considered necessary to know how Husein Muhammad reinterpreted verses of the Qur’an that were considered biased against women. Though his thoughts were widely opposed by the ‘ulama, Husein has given so much to the idea of defending and liberating women from oppression.